Analisis fasilitas tarif pajak penghasilan terutang ditinjau dari penghasilan bruto - Wikardojo, Soko; Mukoffi, Ahmad; Risnaningsih, Risnaningsih; Lero Kaka, Adelsiana (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
National development is a sustainable development related to the whole life of society, nation, and state. National development is supported by several supporting aspects, one of which is tax revenue. This research aims to find out the facility of income tax rate payable in terms of gross income. The type of research used in this research is Interpretive Qualitative data. This Study uses data collection techniques, namely interview techniques, documentation, and observation. The types of data used in this stud are primary data and secondary data. The data analysis technique used is the descriptive analysis technique. The government issued tax law number 36 of 2008 by providing an incentive for tax reduction facilities for taxpayers, as stated in article 31E. The research results show that KPRI Universitas Brawijaya Malang has implemented Article 31E of the PPh Law Number 36 of 2008.